The Role of Cost Management Knowledge as Moderation: Participatory Budgeting, Clarity of Budget Objectives, Managerial Performance - Fadly Aditya (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to examine the effect of participatory budgeting and the clarity of budget targets on managerial performance with knowledge of cost management as a moderator at PT Pupuk Iskandar Muda (PT PIM). The study used data from all employees who have the positions of Assistant Vice President, Vice President, and Senior Vice President at the company PT Pupuk Iskandar Muda. The data collection technique is done by using a questionnaire. The data analysis method in this study uses Moderating Regression Analysis (MRA). Sample data collected were 52 samples from 63 or 82,5%. The results showed that participatory budgeting and clarity of budget targets had a significant effect on managerial performance and that managerial knowledge of cost management could moderate the effect of participatory budgets on managerial performance. On the other hand, this research shows that the knowledge of managerial cost management cannot moderate the effect of the clarity of budget targets on managerial performance.